Cytoplasmic localization of the cell polarity factor scribble supports liver tumor formation and tumor cell invasiveness. Issue 5 (1st April 2018) - Wan, Shan; Meyer, Anne‐Sophie; Weiler, Sofia Maria Elisabeth; Rupp, Christian; Tóth, Marcell; Sticht, Carsten; Singer, Stephan; Thomann, Stefan; Roessler, Stephanie; Schorpp‐Kistner, Marina; Schmitt, Jennifer; Gretz, Norbert; et al.
Abstract : The loss of epithelial cell polarity plays an important role in the development and progression of liver cancer. However, the specific molecular mechanisms supporting tumor initiation and progression are poorly understood. In this study, transcriptome data and immunofluorescence stains of tissue samples derived from hepatocellular carcinoma (HCC) patients revealed that overexpression associated with cytoplasmic localization of the basolateral cell polarity complex protein scribble (Scrib) correlated with poor prognosis of HCC patients. In comparison with HCC cells stably expressing wild‐type Scrib (Scrib WT ), mutated Scrib with enforced cytoplasmic enrichment (Scrib P305L ) induced AKT signaling through the destabilization of phosphatase and tensin homolog (PTEN) and PH domain and leucine‐rich repeat protein phosphatase 1 (PHLPP1). Cytoplasmic Scrib P305L stimulated a gene signature and a phenotype characteristic for epithelial to mesenchymal transition (EMT) and HCC cell invasiveness. Scrib P305L ‐dependent invasion was mediated by the activator protein 1 (AP‐1) constituents ATF2 and JunB through induction of paracrine‐acting secreted protein acidic and cysteine‐rich (SPARC). Coexpression of Scrib P305L and the oncogene c‐MYC through hydrodynamic gene delivery in mouse livers promoted tumor formation and increased abundance of pAKT, pATF2, and SPARC in comparison with controls. Finally, cytoplasmic Scrib localization correlated with AKT and ATF2 phosphorylation in human HCC tissues, and the Scrib P305L ‐dependent gene signature was enriched in cancer patients with poor prognosis. Conclusion: Perturbation of hepatocellular polarity due to overexpression and cytoplasmic enrichment of Scrib supports tumor initiation and HCC cell dissemination through specific molecular mechanisms. Biomarker signatures identified in this study can be used for the identification of HCC patients with higher risk for the development of metastasis. (Hepatology 2018;67:1842‐1856).